Autophagy of Sensory Neurons in the Trigeminal and Dorsal Root Ganglia of Cynomolgus Monkeys (Macaca fascicularis). (January 2020) - Butt, Mark; Fuji, Reina; Reichelt, Mike; Sharma, Alok K.; Cramer, Sarah
Although necrosis and apoptosis are uncommon, autophagy of sensory neurons (ASN) in trigeminal and dorsal root ganglia is a very common, spontaneous finding in cynomolgus monkeys ( Macaca fascicularis ). Data from one author's (Butt) laboratory showed 12 of 22 studies (year range 2017 to 2019) that included the evaluation of sensory ganglia from cynomolgus monkeys had at least one control animal with ASN. Autophagy of sensory neurons is characterized by a distinct cell membrane, cytoplasm filled with autolysosomes, disintegrated nuclear membrane, and/or globules of degraded chromatin. Since these changes are consistent with autophagy and indicate an irreversible state, a diagnosis of autophagy is preferred instead of necrosis or degeneration. Sensory ganglia are not commonly evaluated in nonclinical toxicology investigations so many pathologists may be unaware of this common change. Especially due to the typically small group size of monkey studies, the observation of this change in sensory ganglia may lead to a faulty interpretation that this change is due to the test article. This article describes the light microscopic and ultrastructural characteristics of neuronal autophagy in trigeminal and dorsal root ganglia and provides historical control data of the incidence of this change in cynomolgus monkeys.